If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7x + 3)(x + -5) = 0 Reorder the terms: (3 + 7x)(x + -5) = 0 Reorder the terms: (3 + 7x)(-5 + x) = 0 Multiply (3 + 7x) * (-5 + x) (3(-5 + x) + 7x * (-5 + x)) = 0 ((-5 * 3 + x * 3) + 7x * (-5 + x)) = 0 ((-15 + 3x) + 7x * (-5 + x)) = 0 (-15 + 3x + (-5 * 7x + x * 7x)) = 0 (-15 + 3x + (-35x + 7x2)) = 0 Combine like terms: 3x + -35x = -32x (-15 + -32x + 7x2) = 0 Solving -15 + -32x + 7x2 = 0 Solving for variable 'x'. Factor a trinomial. (-3 + -7x)(5 + -1x) = 0Subproblem 1
Set the factor '(-3 + -7x)' equal to zero and attempt to solve: Simplifying -3 + -7x = 0 Solving -3 + -7x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -7x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -7x = 0 + 3 -7x = 0 + 3 Combine like terms: 0 + 3 = 3 -7x = 3 Divide each side by '-7'. x = -0.4285714286 Simplifying x = -0.4285714286Subproblem 2
Set the factor '(5 + -1x)' equal to zero and attempt to solve: Simplifying 5 + -1x = 0 Solving 5 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1x = 0 + -5 -1x = 0 + -5 Combine like terms: 0 + -5 = -5 -1x = -5 Divide each side by '-1'. x = 5 Simplifying x = 5Solution
x = {-0.4285714286, 5}
| 33.46=7g+3.92 | | 2-0.375x=13 | | 1.14g-8=0.55 | | (10x+4)+(4x-3)=12x+16 | | e^4x=5 | | 2x=3x^2-5 | | -15=3+2x | | 7n+2=4n+18 | | 817/95 | | 5y/3=15 | | z=2+1.75q | | 13x+14=5x+118 | | 3ab+2a=ab | | 180=7y-4 | | b/5+1/7=19 | | 5x^2+24x-12=0 | | 11-9x=24-16x | | 3/8+8m/7=93/56 | | x-8y=4 | | 4/7s=12 | | b/11-5b/11=16/11 | | 5/3y=15 | | 14x-1/2x5 | | -2(r+9)=-27 | | ((n+1)(n+2)(2n+3))/6 | | x=144p/y | | -10(n+10)=-270 | | 3x+16=180 | | 216-2x=180 | | 4x^2-29x-12=0 | | y+75+3y+5=180 | | 8x-5+3=x-7+10 |